TEORIA DA DESCONTAMINAÇÃO NA JURISDIÇÃO SUSTENTÁVEL E PROVA ILÍCITA: DECONTAMINATION THEORY IN SUSTAINABLE JURISDICTION AND ILLEGAL EVIDENCE (Revista Direito em Debate, 2021)
This paper seeks to discuss the contamination of the judge by contact with the illicit evidence, which profoundly affects his conviction and his impartiality. It appears that unlawful evidence is detrimental to the impartiality of the Court, which affects both the plaintiffs and the actual application of the law. In this way, it is sought to understand how the contamination of the judge occurs by the contact with the illicit evidence, and what are the consequences of this phenomenon to the civil process. The theoretical-documentary methodology was used in the paper, with deductive reasoning. It is concluded that the contamination of the judge by the unlawful evidence causes his suspicion, producing relative nullity to the procedure.
Keywords: Unlawful evidence. Principles. Impartiality. Contamination of the judge. Suspicion.